Reliability and validity of a Central Kurdish version of the Dizziness Handicap Inventory - Zmnako, Sherko Saeed F.; Chalabi, Yousif Ibrahim (Scientific reports, 2019)
We cross-culturally adapted the Dizziness Handicap Inventory (DHI) into Central Kurdish dialect (DHI − CK) and verified its reliability and validity. A cross-sectional study was utilised to measure the impacts of vestibular disorders. Along with the DHI − CK, two comparators were introduced: the Visual Analogue Scale and the Clinical Test of Sensory Interaction and Balance. External and internal reliability were tested with intraclass correlation coefficient (ICC) and Cronbach’s alpha/composite reliability, respectively. Patients (n = 301; mean age = 44.5 ± 15.2 years; 59.8% women) presenting with vestibular symptoms for at least 30 days who were diagnosed with a vestibular disorder and healthy participants (n = 43; mean age = 42 ± 17.9 years; 62.8% women) (N = 344). The DHI − CK and its three sub-scales—Physical, Emotional, Functional—exhibited good to excellent external reliability: ICCs in the test-retest were 0.93, 0.88, 0.91, and 0.92, respectively. Cronbach’s alphas were 0.87, 0.71, 0.75, and 0.73, respectively. Convergent validity was supported by Spearman’s correlations between the DHI − CK and the comparators. The receiver operating characteristic curve analysis confirmed discriminating validity. The DHI − CK was cross-culturally validated. It is a reliable and valid tool that can be used by clinicians and researchers to quantify vestibular disorder outcomes in Kurdish - speaking populations.